Penggunaan Media Teka-teki Silang untuk Meningkatkan Hasil Belajar Tematik Siswa Kelas V SDN 33 Mataram - Firdaus, Anggi Mei Ha'an; Witono, A.Hari; Lestari, Sri (TSAQOFAH, 2023)
Learning media is something that can be used to convey information between individuals and groups. So, media involvement in learning can improve student learning outcomes. The problem of the lack of learning media to sharpen students' brains and concentration requires games. The aim of this research is to determine the use of crossword media to improve learning outcomes. This research includes classroom action research using three research cycles. The research was conducted at SDN 33 Mataram with a class V sample of 21 students. From the data obtained, it was concluded that the use of crossword puzzles can improve learning outcomes. Therefore, to create fun learning and can sharpen students' brains and concentration.